2012
DOI: 10.4066/amj.2012.1024
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusion – An unusual cause

Abstract: Hepatitis A (HAV) infection is one of the most common forms of hepatitis in the paediatric age group in developing countries. It is usually self-limiting and rarely accompanied by extra hepatic complication. In this article, we report two children with hepatitis A who had associated issues of pleural effusion and ascites. Both issues improved with resolution of hepatitis after symptomatic treatment. Although uncommon, extra hepatic manifestations can occur with hepatitis A. However, they resolve completely. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…13 Hepatitis A infection-related pleural effusion is a rare extrahepatic manifestation in children. 14 Hepatitis A infection associated with pleural effusion was reported usually on the right side of the lung. 9,11,12 But bilateral effusion has also been documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Hepatitis A infection-related pleural effusion is a rare extrahepatic manifestation in children. 14 Hepatitis A infection associated with pleural effusion was reported usually on the right side of the lung. 9,11,12 But bilateral effusion has also been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Documented case reports of HAV infection with pleural effusions showed that the presence of effusion with HAV infection did not signify poor outcome and it resolves with supportive treatment alone. 6,8,10,11,14,[17][18][19] Though the patient had nearly normal serum bilirubin (1.5mg/dl) and the liver enzymes were highly elevated especially the alkaline phosphatase which was 1000 mg/ dl, but since it is nonspecific to the liver it may not be exclusively signal of liver damage and also the reference range for his age is 93-309 that means 3 to5 times elevated. However, the other enzymes specific to the liver like alanine amino transaminase were also highly elevated.…”
Section: Discussionmentioning
confidence: 99%